Enhancing Promotional Strategies and Customer Profiling for Rural-Based Enterprises in Central Sulawesi and North Maluku - Nanda Alifia Putri; Martdian Ratna Sari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
This community service program was implemented to enhance the marketing capabilities of rural economic actors across several regions in Central Sulawesi and North Maluku, specifically Poso, North Morowali, Banggai, Sigi, Tolitoli, West Halmahera, and South Halmahera. Participants included Village-Owned Enterprises (BUMDes), Toko Tani (Farmer Shop), farmers, and micro-entrepreneurs. Many participants experienced difficulties in identifying their customer segments and implementing effective promotional strategies, and they often relied on conventional marketing methods with limited reach and poorly defined targeting. To address these challenges, selected participants from the regions were brought together for centralized training in Palu using a participatory learning-and-action approach that emphasized customer profiling and promotional strategy development. The results showed measurable improvements in participants’ understanding of promotional concepts, as indicated by an increase in correct post-test responses on promotional tools from 82% to 91%. In addition, early uptake of digital promotion practices was observed, with several participants initiating online product promotion through social media platforms. Overall, the program demonstrates that participatory marketing training can strengthen the customer-oriented capabilities of rural enterprises and support scalable and sustainable community empowerment models in rural areas.